THE ROLE OF TRADE ASSOCIATIONS IN THE PROMOTION OF SUSTAINABILITY: A CASE STUDY OF THE COSMETICS AND CLEANING PRODUCTS ASSOCIATION - ANDI OF COLOMBIA - Valdivieso-Orozco, Viviana (2016)
The paper presents a case study of the sustainability engagement of the Cosmetics and Cleaning Products Association – ANDI of Colombia. It provides empirical evidence of the potential that trade associations have for promoting sustainability in their sectors, and also of the specific roles that they can play, specifically in the Colombian context. The data helps to understand the reasons behind the strategic decision of these organizations to work in sustainability and shows ways in which trade associations can address the factors that might impede them from increasingly engaging and from having an impact.